(untitled) - Masudur Rahman; Valliappan Raju (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this paper is to develop a model that constructs relations amongst TQM practices and patient satisfaction, particularly in the context of Bangladesh public healthcare, through an empirical study. However, the research on the field of TQM practices and its impact on patient satisfaction and hospital performance are available around the world, the implementation of TQM practices is not well established in hospitals in Bangladesh. For closer analysis of its linking, relations amongst individual TQM practices and patient satisfaction as a measure of success was specifically investigated. Asurvey was carried out and 384 responses were obtained from the inpatients receiving medical treatment of 2 tertiaries and 1 secondary-level hospitals using self-administered questionnaire. Contributing to the analysis was a set of 7 TQM constructs. The main factor of data analysis was completed to test hypotheses about individual TQM practices by using multiple regression. Moreover, structural equation modeling (SEM) was used to define relations amongst TQM practices and patient satisfaction. Overall, the findings showed a positive and significant relations amongst the TQM practices and patient satisfaction. The study also showed that top management commitment (TMC) was considered to be the most predominant TQM activities associated with patient satisfaction.